Assessment of patients with acute abdominal pain. Issue 6 (June 2013) - Jandoo, Rajan; Lawrence, Matthew
Abdominal pain is a common presenting symptom to the GP surgery and can be particularly challenging when trying to decide whether the symptoms are severe enough to warrant a hospital admission. Patients with acute and severe abdominal pain often require urgent surgical intervention and being able to recognise these patients is extremely important. This article will revise the features in the history and examination pointing towards a more serious cause and help discriminate between those patients who can be managed entirely in primary care. It will provide a brief overview of the management of these patients in hospital and their care after discharge.